Desenvolvimento de cimentos ósseos à base de Biosilicato - Machado, Caroline Vital Rosa (2020)
Synthetic grafts have an important contribution to modern health care, especially in bone reconstruction surgeries. In addition orthopedics, bone grafts can also be used in maxillofacial surgery. In 1980s, bone cements emerged as an alternative to grafts in granular or block form. Bone cements have advantages, such as moldability to the fracture or injury region and possibility of treating comminuted fractures, in addition to allowing minimally invasive surgical procedures. In this work, new compositions were prepared to obtain a bone cement that combines good fracture strength and bioactivity, in addition to a good workability and setting time between 5 and 20 minutes. To achieve this goal, a bioactive glass-ceramic Biosilicate® (developed at LaMaV/UFSCar) and different types of phosphates were used. Scanning Eletron Microscopy (SEM) analyses were used as a tool to control the formation of hydroxycarbonate apatite (HCA) after exposing the samples to a SBF-K9 (Simulated Body Fluid) solution. The crystalline phases formed were identenfied by X-ray Diffraction. Additionally, biaxial flexion tests were conducted to obtain the fracture resistance. The bioactivity of the cements was evaluated by in vitro bioactivity tests, followed by Fourier Transformed Infrared Spectroscopy (FTIR) analysis, confirmed the formation of a HCA bioactive layer, indicating the good in vitro bioactivity of the material. It was also found that the addition of additives influenced directly in the cement reactions, and that the sample containing hydrochloric acid showed the best results (~ 30 MPa after 14 days of setting). Exposure to the SBF-K9 solution did not drastically affect the fracture strength. Thus, a new cement with great potential for use as bone graft was developed in this work. In vivo and clinical tests will be necessary before commercial production and application in humans.